The Classroom as Studio—The Studio as Classroom (LEARNing Landscapes, 2008)
In this article a studio approach to teaching is examined. Based on her own pedagogical experience, the author shows how the "classroom as studio" and "studio as classroom" become a home for rich learning both within and beyond the classroom walls. She observes that through the skills, work ethic, processes, and discipline inherent to the arts, students develop the competencies that transfer easily across disciplines. Further, she demonstrates that the creative and natural language of movement and dance, in conjunction with a supportive studio atmosphere, can serve as a strong pedagogical equalizer that enables each student to flourish in an uninhibited way.
Keywords: classroom; studio; dance; movement; competency